Fenomenologi-Ekonomi Islam: Lit Review atas Epistemologi Ekonomi Islam Masudul Alam Choudhury - Shalihin, Nurus (AL-FALAH : Journal of Islamic Economics, 2017)
Islamic economics is difference with the positivism economics and others. It is a established-concessus among Muslim-economists. Albeit some scholars are still sceptical toward Islamic economics as a complete-science. To respond this assumption, various Islamic scholars who are concern in formulating the epistemology of Islamic Economics. Turast written by classical muslim scholars studied intensively. And also Masudul Alam Choudhury who have intensively research the epistemology of Islamic economics with uniqueness form of epistemologyânamed by the phenomenology of Islamic economics. This paper examine radically the essensy of Masudul Alam Choudhury. It is to identify the construction of Islamic economics metodology offered by Choudhury. Keywords : Phenomenology, Unity of Knowledge, Islamic Economics, Phenomenology methodology and logical formalism.